Examination of Turkey’s and European Union Member States’ Health Indicators with Multidimensionel Scaling - Sigirli, Deniz; Ediz, Bulent; Cangur, Sengul; Ercan, Ilker; Kan, Ismet (Annals of Medical Research, 2021)
None
Keywords: Multidimensional scaling, Health indicators, Euclidian space